THE STEREOTYPE TOWARDS WOMAN REFLECTED IN THE NOVEL “ON THE COME UP” BY ANGIE THOMAS - Mutia Rafael; Tomi Arianto (Universitas Putera Batam, 2021)
Stereotypes created by society toward women still can be found around. Women could not be leaders, could not have a decent job, did not have to have high education, and their position only to please their family. In this research the researcher is discussing about stereotypes that happened towards women. By using Barbara Walter's theory, where it is portrayed how men find women should be under their position whether in work position or in general, this study is examined. The method used in this research is qualitative method, where the data taken from sentences or conversations from the novel On the Come Up by Angie Thomas. The results of this study indicate the main character is not following the stereotypes that society has created. It can be concluded that she is not the ideal type based on societal stereotypes.